2018
DOI: 10.3389/fphys.2018.01569
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and Oxidative Stress: Focus in Obese Pregnancies

Abstract: The prevalence of obesity in women of childbearing age around the globe has dramatically increased in the last decades. Obesity is characterized by a low-state chronic inflammation, metabolism impairment and oxidative stress, among other pathological changes. Getting pregnant in this situation involves that gestation will occur in an unhealthy environment, that can potentially jeopardize both maternal and fetal health. In this review, we analyze the role of maternal obesity-induced oxidative stress as a risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 115 publications
0
24
0
Order By: Relevance
“…In relation to other pregnancy-associated disorders, a reduced enzymatic capacity and increased oxidation has been demonstrated in placenta tissue from preeclamptic women, contributing to the pathogenesis of this gestational disorder [49]. On the other hand, increased oxidative stress in late gestation was observed in several pregnancy-related disorders in association with increased trophoblast apoptosis and altered placental vascular endothelium [50]. Meanwhile, other promising studies have revealed the presence of possible alterations in ROS/SOD ratio based on upregulation of the SOD along with the activation of the superoxide anion degradation pathway at the vascular level in cardiovascular diseases [51].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to other pregnancy-associated disorders, a reduced enzymatic capacity and increased oxidation has been demonstrated in placenta tissue from preeclamptic women, contributing to the pathogenesis of this gestational disorder [49]. On the other hand, increased oxidative stress in late gestation was observed in several pregnancy-related disorders in association with increased trophoblast apoptosis and altered placental vascular endothelium [50]. Meanwhile, other promising studies have revealed the presence of possible alterations in ROS/SOD ratio based on upregulation of the SOD along with the activation of the superoxide anion degradation pathway at the vascular level in cardiovascular diseases [51].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of obese pregnant women has steadily increased worldwide in recent years 34 . Obesity leads to pregnancy development under suboptimal conditions because of chronic inflammation, oxidative stress, metabolic insufficiency, and insulin resistance 35 . The chronic inflammation caused by obesity deregulates the immune tolerance between mother and fetus, and it could be a possible explanation for the increased sCEACAM1 concentration in high‐risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these numbers lies in the fact that pregestational obesity has been linked to an increased risk of adverse outcomes at every stage of pregnancy, including periconceptional difficulties and health consequences in the newborn [ 3 , 4 , 5 , 6 , 7 ]. During gestation, obese mothers have a higher risk of spontaneous and recurrent pregnancy loss [ 8 ], preeclampsia and gestational diabetes mellitus [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress (OS) has been proposed as a common underlying mechanism for malformations induced by either maternal diabetes or obesity [ 7 , 18 , 19 ]. Both obesity and pregnancy are, per se , situations characterized by an imbalance between the production of reactive oxygen species and their elimination by antioxidant defenses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation